Who look at me?! : shifting the gaze of education through blackness, queerness, and the body - Callier, Durell M.; Hill, Dominique C. (Personal/public scholarship, 2019)
Who Look at Me?!: Shifting the Gaze of Education through Blackness, Queerness, and the Body explores how we, as a society, see Blackness and in particular Black youth. Drawing on a range of sources, the authors argue that the ability to operationalize the sentiment that #BlackLivesMatter, requires seeing Blackness wholly, as queer, and as a site of subversive knowledge production. Continuing the work of June Jordan and Langston Hughes, and based on their work as a Black queer artist collective known as Hill L. Waters, Who Look at Me?! provides alternative tools for reading about and engaging with the lived experiences of Black youth and educational research for and about Black youth. In this way, the book presents not only the possibilities of envisioning teaching and research practices but presents examples that embrace, celebrate, and make room for the fullness of Black and queer bodies and experiences. This work will appeal to those interested in emancipatory methodological and educational practices as well as interdisciplinary conversations related to sociocultural constructions of race and sexuality, politics of Blackness, and race in education.